Comparative Analysis of R&D in the Visegrad Group Countries in the Years 2004-2018 - Małgorzata Jabłonśka (Comparative Economic Research. Central and Eastern Europe, 2020)
The purpose of this paper is to present a comparative analysis of basic measures that demonstrate the development of R&D in the Visegrad Group countries (Poland, the Czech Republic, Hungary, and Slovakia) in the years 2004-2018. The preliminary anal- ysis of the problem allowed for the formulation of a research hypothesis, which reads: Since becoming a member of the EU, the innovation of the economies of the Visegrad Group countries has improved. The analysis shows that the structure and dynamics of R&D expenditure in these countries are diverse, although the innovation potential of the regions of the Visegrad Group countries is still low compared to the average EU level.
Keywords: G30; G10; O16; K40; 330; innovativeness; R&D; Visegrad Group; economy